2023
DOI: 10.3389/fendo.2023.1140886
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal exposure to the fungicide ketoconazole alters hypothalamic control of puberty in female rats

Abstract: IntroductionEstrogenic endocrine disrupting chemicals (EDCs) such as diethylstilbestrol (DES) are known to alter the timing of puberty onset and reproductive function in females. Accumulating evidence suggests that steroid synthesis inhibitors such as ketoconazole (KTZ) or phthalates may also affect female reproductive health, however their mode of action is poorly understood. Because hypothalamic activity is very sensitive to sex steroids, we aimed at determining whether and how EDCs with different mode of ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 108 publications
0
3
0
Order By: Relevance
“…The same pattern was seen in animals exposed to DES-0.048 during adulthood. Hypothalamic GnRH secretion was not affected in these females ( 16 ). Unfortunately, we do not have measurements of luteinizing hormone/follicle stimulating hormone and it is therefore difficult to deduce if observed ovarian changes are associated with local and/or central effects of DES.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…The same pattern was seen in animals exposed to DES-0.048 during adulthood. Hypothalamic GnRH secretion was not affected in these females ( 16 ). Unfortunately, we do not have measurements of luteinizing hormone/follicle stimulating hormone and it is therefore difficult to deduce if observed ovarian changes are associated with local and/or central effects of DES.…”
Section: Discussionmentioning
confidence: 78%
“…Using two compounds that we know have endocrine disrupting effects in humans enables comparison of the two exposure windows, as well as endpoint sensitivity using an established OECD test guideline ( 3 ). Perinatal exposure to these endocrine disruptors has been shown to affect reproductive development ( 1 , 2 , 16 , 17 ) and they are expected to display different effect patterns depending on age at exposure start.…”
Section: Introductionmentioning
confidence: 99%
“…Several experimental studies on rats have reported that perinatal, juvenile, or adult exposure to EDCs, disrupt the hypothalamic control of pituitary gonadotropin synthesis leading to a disruption of gonadal steroid production and androgens cyclicity ( 58–62 ). These studies suggest that EDCs exposure affects the expression of GnRH and kisspeptin, influences the pulsatile launch of GnRH, and interferes with the regulation of gonadotropin production from the pituitary axis ( 63 ).…”
Section: Physiological Effects Of Edcs On Male Infertilitymentioning
confidence: 99%